# How do you solve #abs(-2x+4)=6#?

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation abs(-2x + 4) = 6, you first isolate the absolute value expression, then solve for x.

- Split the equation into two cases: -2x + 4 = 6 and -2x + 4 = -6.
- Solve each case separately for x. Case 1: -2x + 4 = 6 Case 2: -2x + 4 = -6
- Simplify each equation and solve for x. Case 1: -2x = 2 Case 2: -2x = -10
- Divide both sides of each equation by -2 to isolate x. Case 1: x = -1 Case 2: x = 5
- Verify the solutions by substituting them back into the original equation.

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7